POTENTIAL DEVELOPMENT of GOAT - Mohamad Jen Wajo; Stepanus Pakage; Denny Anjelus Iyai; Novyanti Novyanti (Perkumpulan Dosen Muda (PDM) Bengkulu, 2020)
The main objective of this research was tostudythe potential of goatlivestock developmentinthe Districtof BomberayWest Papua. Descriptivestudy was conductedusingsurvey and interviews. The results showedthat theBomberay area has potential for goat development. This can be seen from land availability, sufficient and for age available production, knowledge and motivation levels,kept farmers ranchers, as well as provide economic benefits tofarmers. Breedof goats warenative goatsand cross breed of Etawa goat. Production and reproductive performance was quite good.The main objective of this research was tostudythe potential of goatlivestock developmentinthe Districtof BomberayWest Papua. Descriptivestudy was conductedusingsurvey and interviews. The results showedthat theBomberay area has potential for goat development. This can be seen from land availability, sufficient and for age available production, knowledge and motivation levels,kept farmers ranchers, as well as provide economic benefits tofarmers. Breedof goats warenative goatsand cross breed of Etawa goat. Production and reproductive performance was quite good.